Variability of air quality and bioclimatic conditions in urban area: Case study of Lublin - Dobek, Mateusz; Wereski, Sylwester; Krzyżewska, Agnieszka (Quaestiones Geographicae, 2023)
The paper analyses biometeorological conditions in Lublin based on the Universal Thermal Climate Index (UTCI), and air quality based on the Common Air Quality Index (CAQI). The used data were obtained from the database of IMGW-PIB and RDEM, and cover the period 2015–2021. The most frequently occurring biometeorological conditions were classified as no thermal stress. They were observed with a frequency of 34.3%. Conditions unfavourable for the human organism accounted for 65.7% in total, including those belonging to thermal stress classes related to cold stress (52.3%), and heat stress (13.4%). In the analysed years, 75.5% of cases were with very low and low air pollution. High and very high air pollution usually occurred during biometeorological conditions related to cold stress (from slight cold stress to strong cold stress). During extreme thermal phenomena, such as a cold wave (January 2007) and hot wave (August 2015), unfavourable biometeorological conditions were accompanied by low aerosanitary conditions (low air quality). In the analysed period, and particularly in recent years, an improvement in air quality has been observed, potentially associated with limited mobility of people during the COVID-19 pandemic.